The Application of Government Accounting Standards and Quality of Financial Reports on the Accountability Financial Performance - Indra; Febrian, Mutiara Adinda; Putri, Septia Amelia (Ilomata International Journal of Tax and Accounting, 2024)
This research aims to see the effect of implementing Government Accounting Standards and the Quality of Financial Reports on the Accountability of Financial Peformance of the Tanjungpinang City Government. The population in the study was 99 respondents and a research sample of 50 respondents was obtained using the slovin formula with a tolerance level of 10%.The research method used is a quantitative research method. The type of data used is primary data, the data collection technique uses a questionnaire with a likert scale, and the data is processed using the JASP statistical application version 0.17.2.1. The results of the analysis show that all variables have partial or simultaneous influence, seen from all variables, the calculated t is greater than the t table, and the calculated f is greater than the f table, with an overall influence of 74,5% and the remaining 25,5% is influenced bye other variables outside this research.